A reappraisal of Maxillaria (Orchidaceae) - Schuiteman, Andre; Chase, Mark (Phytotaxa, 2015)
It is argued that a broad and expanded circumscription of Maxillaria is to be preferred over a narrower one that necessitates the recognition of many segregate genera. These more narrowly circumscribed genera are often difficult to diagnose, increasing the risk of misidentifications, especially when material is only identified to genus level. The genera of the Maxillaria alliance as recognised in Genera orchidacearum are treated as sections of an expanded genus Maxillaria. Cryptocentrum, Cyrtidiorchis, Mormolyca, Pityphyllum, and Trigonidium are here included in Maxillaria. Criteria for generic delimitation are discussed, the necessary combinations are made, and a key to the sections as well as a provisional checklist of the 634 species of Maxillaria arranged according to section are provided. Maxillaria prolifera is shown to be the correct name for M. pendens. Maxillaria humilis is a new combination for M. gracilis.